2022
DOI: 10.1091/mbc.e22-05-0153
|View full text |Cite
|
Sign up to set email alerts
|

Acentrosomal spindle assembly and maintenance in Caenorhabditis elegans oocytes requires a kinesin-12 nonmotor microtubule interaction domain

Abstract: In Caenorhabditis elegans oocytes, kinesin-12/KLP-18 is the major force-generating motor that promotes spindle bipolarity. A combination of in vitro and in vivo approaches is used to gain insight into the mechanisms by which KLP-18 and its adaptor MESP-1 promote spindle assembly, and it is shown that KLP-18 is also continuously required to maintain bipolarity.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 82 publications
0
4
0
Order By: Relevance
“…Our hypothesis that outward forces are activated upon ZYG-8 depletion raised the possibility that this protein may normally suppress a factor that generates these forces. Since KLP-18/kinesin-12 provides the major outward sorting force in C. elegans oocytes (Wolff et al, 2016; Wolff et al, 2022b), we first sought to explore the possibility that ZYG-8 regulates KLP-18. To this end, we co-depleted KLP-18 and ZYG-8, to determine if there was evidence for excess outward force under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our hypothesis that outward forces are activated upon ZYG-8 depletion raised the possibility that this protein may normally suppress a factor that generates these forces. Since KLP-18/kinesin-12 provides the major outward sorting force in C. elegans oocytes (Wolff et al, 2016; Wolff et al, 2022b), we first sought to explore the possibility that ZYG-8 regulates KLP-18. To this end, we co-depleted KLP-18 and ZYG-8, to determine if there was evidence for excess outward force under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…However, mechanisms must also exist to limit these outward forces, so that the spindle can remain stable after it forms ( Figure 8A ). Previous studies revealed that KLP-18/kinesin-12 and BMK-1/kinesin-5 produce outward forces, while dynein produces a counter-balancing inward force Wolff et al, 2016; Cavin-Meza et al, 2022a; Wolff et al, 2022b). We have now identified ZYG-8 as another factor that is important for this force balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of factors required for acentrosomal spindle assembly and pole formation in C. elegans have been identified: MEI-1/2 katanin promote the generation of short microtubules [4], KLP-15/16 bundle these microtubules [5,6], KLP-18 and MESP-1 sort microtubules to establish bipolarity [3], ASPM-1 binds to microtubule minus ends and functions to focus the spindle poles in conjunction with dynein [7,8], and KLP-7 MCAK acts to limit the number of spindle poles and inhibit excess microtubule nucleation [2,9,10]. Rapid inactivation or depletion of MEI-1, KLP-18, or dynein causes defects in spindle structure [8,11,12], demonstrating that these factors are required for spindle maintenance. However, whether any other pole associated-proteins stabilize the spindle to maintain bipolarity is not known.…”
Section: Introductionmentioning
confidence: 99%